EVIL COMPUTER SYSTEM - RISTYAWATI RISTYAWATI RISTYAWATI (Majalah SIKOMTEK, 2006)
Computer crime can be categorized as crimes of "White Colar Crime", which operates inmore use of the mind or brain. Definition of Cyber crime is any act that harm others orcertain parties who performed on digital media or with the aid of digital devices.